Paleomagnetism of the Mesozoic Coast Parallel Dolerite Dikes of West Greenland - Fahrig, W. F.; Freda, G. (Canadian Journal of Earth Sciences, 1975)
Paleomagnetic measurements on 61 drill cores from eight sites of the Coast Parallel dikes of west Greenland (Fiskenaesset area) have yielded a pole position at 169°E, 54°N, α 95 = 5.9°. When these data are combined with those from the Nunarsuit-Tornarssuk area (Ketelaar 1963) the pole is 168°E, 56°N, α 95 = 6°. Reversely magnetized dikes are present in both areas.The Coast Parallel dike pole lies close to the Triassic pole position for North America if corrected for Bullard's fit. The dikes were therefore intruded prior to the Mesozoic separation of Greenland and North America.